2017
DOI: 10.1002/jmr.2630
|View full text |Cite
|
Sign up to set email alerts
|

Ion cum molecularly dual imprinted polymer for simultaneous removal of cadmium and salicylic acid

Abstract: Ion cum molecularly dual imprinted polymer (DMIP) was synthesized for the simultaneous removal of salicylic acid (SA) and cadmium (Cd) by suspension polymerization method using chitosan (CTS) as functional polymer, epichlorohydrin as cross-linker, and 4-hydroxy benzoic acid (4HBA) as well as Cd as organic and inorganic templates, respectively. Use of the dummy template 4HBA during the synthesis of DMIP had the advantage of creating imprinted cavities in DMIP, which depicted good uptake for SA. Scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 67 publications
(126 reference statements)
0
9
0
Order By: Relevance
“…Rahangdale et al [16] reported a study about molecularly dual imprinted polymeric material for the removal of cadmium by suspension polymerization. Scanning electron microscopy, swelling study and Fourier transform infrared spectroscopy indicated successful polymerization of the dual-ion imprinted polymeric material.…”
Section: Removal Of Metal Ions With Imprinted Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahangdale et al [16] reported a study about molecularly dual imprinted polymeric material for the removal of cadmium by suspension polymerization. Scanning electron microscopy, swelling study and Fourier transform infrared spectroscopy indicated successful polymerization of the dual-ion imprinted polymeric material.…”
Section: Removal Of Metal Ions With Imprinted Materialsmentioning
confidence: 99%
“…The polymers are prepared in the presence of the ions. When the template is removed, specific cavities show high selectivity to the desired metal ion [16,17]. Studies on metal ion-imprinted polymers have been increasing over the years as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that salicylic acid and its derivatives in organic aprotic solvents form both intramolecular and intermolecular hydrogen bonds between the phenolic hydroxyl and the neighboring carbonyl group [13][14][15][16]. We note that the intramolecular hydrogen bond is predominantly formed at low concentrations and the intramolecular hydrogen bond at high concentrations [14][15][16]. During the presence of an intramolecular hydrogen bond in salicylic acid, the stability of monomeric complexes was confirmed by molecular modeling.…”
Section: Results and Discussion Of Ir Spectra Of Native Compounds Formentioning
confidence: 99%
“…During the presence of an intramolecular hydrogen bond in salicylic acid, the stability of monomeric complexes was confirmed by molecular modeling. A comparative analysis of IR spectra of salicylic and acetylsalicylic acids and methyl salicylate showed that the absorption band of OH groups participating in intramolecular hydrogen bond is 3230 cm À1 and the complex spectrum in the range 2500-3300 cm À1 characterizes the absorption of dimers [14][15][16][17]. The mechanism of formation of dimeric products from an intermediate reactive compound obtained as a result of disproportionation is discussed [17].…”
Section: Results and Discussion Of Ir Spectra Of Native Compounds Formentioning
confidence: 99%
“…The drug had affinity to the MIP and it was released from the matrix due to ambient conditions where pH played a crucial role. In a work by Rahangdale and coworkers, chitosan was stabilized by crosslinking using epichlorohydrin [43]. Salicylic acid and cadmium were imprinted into the membrane and it exerted a binding capacity 38 respective 24 mg/g for cadmium respective salicylic acid.…”
Section: Membranes For a Template Imprintingmentioning
confidence: 99%